2020
DOI: 10.1007/s43465-020-00254-9
|View full text |Cite
|
Sign up to set email alerts
|

Setting Up 3D Printing Services for Orthopaedic Applications: A Step-by-Step Guide and an Overview of 3DBioSphere

Abstract: Introduction 3D printing has widespread applications in orthopaedics including creating biomodels, patient-specific instruments, implants, and developing bioprints. 3DGraphy or printing 3D models enable the surgeon to understand, plan, and simulate different procedures on it. Despite widespread applications in non-healthcare specialties, it has failed to gain traction in healthcare settings. This is perhaps due to perceived capital expenditure cost and the lack of knowledge and skill required to execute the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Rapid development of 3D printing technology has led to its increasing application in orthopaedics (33)(34)(35)(36)(37)(38)(39)(40)(41)(42). Type and complexity of fractures vary from person to person.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid development of 3D printing technology has led to its increasing application in orthopaedics (33)(34)(35)(36)(37)(38)(39)(40)(41)(42). Type and complexity of fractures vary from person to person.…”
Section: Discussionmentioning
confidence: 99%
“…This may have to do with the fact that additional data supporting the need for 3D printing should be established. It has been suggested by Shah et al that when this additional data support is gathered, insurance companies can then create a dedicated Current Procedural Terminology (CPT) code for 3D printing, thus allowing for a more widespread use of this technology [ 64 ]. As for the manpower, there is a necessity for skilled users, who can either be technicians or surgeons who would have to undergo extensive training in medical modeling software modalities, which adds to the cost of this process [ 27 , 32 , 65 ], especially since the very nature of medical 3D printing often requires customization, meaning skilled users must be able to convert clinical data into digital models tailored to each patient’s unique requirements.…”
Section: Reviewmentioning
confidence: 99%
“…Shah et al [ 19 ] and Kabra et al [ 4 ] and various other research groups in the field have emphasized the cost implications linked to 3D printing. Tetsworth et al concluded that while the initial cost of 3D printing may be too high for surgeons in developing countries, as 3D printer prices decrease, the ability to create prototypes and patient-specific models will become more affordable [ 1 ].…”
Section: Cost and Regulatory Aspects Of 3d Printing In Orthopedicsmentioning
confidence: 99%